"Zdejmij okulary różowe!" - błędy w szyku zdania w polszczyźnie studentów ukraińskojęzycznych = "Take off your glasses rose-coloured!" - on word order errors made by Ukrainian-speaking students in Polish - Izdebska-Długosz, Dominika (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article presents a syntax error made by Ukrainian-speaking learners of Polish. Word order errors have been divided into a few smaller categories. From the perspective of effective communication, word order errors do not hinder the mutual understanding of the interlocutors. Therefore, course books and other Polish as a Foreign Language teaching aids marginalise the question of word order in Polish.
Keywords: szyk zdaniowy; błędy językowe; Ukraińcy; język polski jako obcy; word order; linguistic errors; Ukrainians; Polish as a Foreign Language